Kingdom of the Netherlands-Aruba : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2010)
The note gives statistical data on Aruba with regard to indicators of tourism activity, components of GDP, real GDP, contributions to real GDP, growth, changes in consumer price index, and legal minimum wages. The statistical data of operations of the central government, operational budget of the social insurance bank, financial balance, balance of payments summary, non-oil balance of payments summary are detailed. The balance sheets of bank-like institutions, life insurance companies, and pension funds are given along with utilities housing mortgage statistics.